(untitled) (diségno, 2022)
The central role of archival drawings as primary evidence for the history of architecture, landscape, cities and infrastructures has long been a clear fact. As Manfredo Tafuri affirms, “architectural drawings, interpreted precisely as archaeological traces, from which a text is decomposed, also serve to ‘disseminate’ the work […] to the point of telling us something more about that work, as if the work alone did not speak sufficiently” [Tafuri 1983, p. 24]; also according to Tafuri, “a drawn work or a cycle of drawings of an architecture can even modify the reading of another work” [Tafuri 1983, p. 25]. [read more]